3D Porous Copper Films with Large Specific Surface Prepared by Hydrogen Bubble Template - Luo, Binbin; Li, Xueming; Li, Xianli; Feng, Wenlin (Asian Journal of Chemistry, 2013)
Three dimensional copper films with large specific surface were fabricated by electrochemical deposition using hydrogen bubble as a dynamic template. X-Ray powder diffraction, scaning electron microscopy and Brunauer-Emmett-Teller (BET) techniques were employed to characterize the samples. The pore sizes and branch sizes are tunable by adding poly(ethylene glycol) (PEG) and chloridion, respectively. Because PEG as bubble stabilizer alters the surface tension of the sol/gas and suppresses the coalescence of bubbles, while the complex effect of chloridion leads the branch sizes to decrease. For example, the surface pore size was reduced from 100 μm to about 15 μm by adding 0.48 g L-1 PEG 10000, while adding 150 mg L-1 chloridion, the average size of the branches in the film was reduced prominently and became much denser. According to the Brunauer-Emmett-Teller method, porous copper exhibits large specific surface area of 2.1120 m3 g-1 when pore diameter of prepared porous copper is at 15 μm, while main pore size distribution rarely changed when adjusting the concentration of PEG 10000.